Wind loads prediction using LES: Inflow generation, accuracy and cost assessment for the case of Torre Gioia 22. (1st July 2022) - Xing, Jin; Patruno, Luca; Pozzuoli, Chiara; Pedro, Gonçalo; de Miranda, Stefano; Ubertini, Francesco
Abstract: In this paper, Large Eddy Simulations, LES, are used in order to evaluate wind loads on a recently designed high-rise building located in Milan, Italy. The selected case study is taken as an example of a typical wind loading assessment, characterized by a complex geometry due to both the shape of the tower and the presence of surroundings. Firstly, the sensitivity of the results to the adopted mesh is analysed. Then, results are compared to wind tunnel measurements and the economical viability of such kind of simulations is discussed. The paper aims at providing an overview of the main factors which can contribute to the success of such analyses and evaluate their accuracy. Not specialized readers will hopefully gain a better insight into the critical aspects which characterize such simulations, while the interested readers will find numerous practical considerations useful for their setup. Highlights: Large Eddy Simulations are performed on a newly designed tower. The analyses setup and the inflow generation are detailed. Results are discussed in terms of peak values and global forces. The economical viability of CFD simulations is discussed.